Is All Punishment Local? The Effects of Jurisdictional Context on Sentence Length*. (22nd February 2013) - Chen, Elsa Y.
<x xml:space="preserve">Abstract</x> Objectives This article investigates the extent to which contextual and individual factors influence the length of prison sentences in California. Methods The analysis applies a hierarchical linear model to individual and county‐level data. Results Some characteristics of the racial, organizational, and public safety environments are found to influence the length of prison terms. Conclusions The findings support the organizational maintenance perspective and the idea of minority incarceration as a response to a perceived crime threat. Political environment is not found to have a significant effect on sentence lengths, and the findings do not support the racial threat hypothesis. The effects of contextual factors are more modest than those of individual attributes, including legally relevant variables, such as offense severity, prior record, parole status, and three strikes eligibility. African‐American and younger offenders receive longer sentences, but this effect is not found for Latinos. Substantive, methodological, and policy implications are discussed.